2013
DOI: 10.1155/2013/564392
|View full text |Cite
|
Sign up to set email alerts
|

Cone Beam Computed Tomography Evaluation of the Diagnosis, Treatment Planning, and Long-Term Followup of Large Periapical Lesions Treated by Endodontic Surgery: Two Case Reports

Abstract: The aim of this case report is to present two cases where cone beam computed tomography (CBCT) was used for the diagnosis, treatment planning, and followup of large periapical lesions in relation to maxillary anterior teeth treated by endodontic surgery. Periapical disease may be detected sooner using CBCT, and their true size, extent, nature, and position can be assessed. It allows clinician to select the most relevant views of the area of interest resulting in improved detection of periapical lesions. CBCT s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 15 publications
(38 reference statements)
0
15
0
1
Order By: Relevance
“…They highlighted that CBCT was found to be an accurate diagnostic method to identify large periapical lesions based on the gray-scale value. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…They highlighted that CBCT was found to be an accurate diagnostic method to identify large periapical lesions based on the gray-scale value. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Shekhar and Shashikala (18) reported that CBCT scan may be regarded as a more accurate method in differentiation between a solid from a fluid-filled large periapical lesion or cavity as compared to conventional intra-oral periapical radiographs (18) .…”
Section: Discussionmentioning
confidence: 99%
“…When a radiotransparent periapical lesion measures over 8 to 10 mm in diameter [ 1 ] and it is a suspected periapical cyst, endodontic surgery is required to remove the cyst and a biopsy is needed to confirm histologic diagnosis of the lesion [ 2 ].…”
Section: Introductionmentioning
confidence: 99%